Kemudahan, Keamanan, dan Pengalaman Pengguna: Faktor Penentu Minat Konsumen dalam Menggunakan E-Wallet - Annisa Bilkhisti; Anggita Refany Pramudya; Chaterine Ratu Rebecca Sirait (Journal of Economic and Business Advancement, 2025)
This study examines the determinants of consumer interest in using e-wallets by focusing on three core variables: perceived ease of use, security, and user experience. The findings reveal that ease of use significantly increases user willingness to adopt digital payment platforms, particularly when applications offer simple navigation, quick processes, and intuitive interfaces. Security also plays a central role, as strong protection systems such as encryption and multilayer authentication enhance user trust and reduce perceived risks associated with digital transactions. User experience emerges as a decisive factor that integrates technical performance, interface quality, personalization, and seamless transaction flow into a holistic digital interaction that strengthens satisfaction and long-term engagement. The synergy of these three variables generates a positive perception of e-wallet reliability and convenience, thereby influencing users to adopt and continuously use digital payment services. Overall, the study highlights that consumer interest is shaped not by a single factor but by the combined effects of convenience, safety, and meaningful digital experiences.